Lung Diseases: Chronic Respiratory Infections - Francesco B. Blasi (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Both chronic and acute infections play a significant role in the pathogenesis and clinical course of chronic obstructive pulmonary disease (COPD) and both cystic fibrosis (CF) and non-CF bronchiectasis. There is also specific evidence that chronic infection, even in the absence of acute infection, has an influence on the manifestations and disease course. The infections found in COPD, CF, and bronchiectasis share a number of clinical similarities, the most striking of which are bacterial persistence despite the use of antibiotics and antibiotic resistance. In the last two decades, the rate of antibiotic resistance has increased dramatically and poses serious threats for patients and public health. There are different reasons for this increase in resistance, but the overuse of antibiotics in the community is certainly the most prominent. On the other hand, the chronic use of antibiotics in chronic diseases like COPD, CF, and bronchiectasis is also potentially associated with an increase in MDR pathogens. During the last decade, a growing interest has been raised in evaluating nontuberculous mycobacteria's role in chronic respiratory diseases like bronchiectasis.